Role of Color Doppler and Three-dimensional Ultrasound in Infertility (Faridpur Medical College Journal, 2019)
Color Doppler is emerging as a valuable diagnostic imaging modality in the field of medicine, primarily infertility. Reproductive disorders, including infertility and spontaneous abortions/miscarriages, have emerged as major public health problem(s) worldwide. Color Doppler energy imaging is a high throughput technology based on the total integral of energy frequency spectrum. Color Doppler is a high-throughput, sophisticated imaging technique for the assessment of uterine anomalies, intrauterine pathology, tubal patency, polycystic ovaries, ovarian follicular monitoring, endometrial receptivity, failed or an ectopic pregnancy, male infertility and uterine, endometrial and ovarian vascularity. Assessments of the utero-ovarian pulsatility indices (PIs), resistance indices (RIs), and endometrial color signals are important determinants of in vitro fertilization (IVF) cycles and pregnancy rates. With many clinical/scientific research experience in the field of reproductive medicine, I strongly believe that an overall public health model needs to be designed in managing infertility patients; therefore, major issues such as cost effectiveness and technical artifacts should address so as to achieve an accurate clinical diagnosis, successful IVF outcome/pregnancy, and overall patient satisfaction in a clinical rehearse setting. Simple, safe efficient and affordable diagnostic modalities should be incorporated at infertility clinics coupled with well-designed patient counseling sessions and community-based public health awareness campaigns conducted so as to reduce the morbidity and mortality rates associated with reproductive disorders. Three dimension (3-D) ultrasound is a new imaging modality which is being introduced into clinical practice. It has been proved that 3-D ultrasound is a very highly reproducible technique. With 3-D ultrasound, a volume of a region of interest can be acquired and stored. This volume can be further analyzed in several ways, such as navigation, multiplanar display and surface rendering or volume calculation. Power Doppler ultrasound, in combination with 3-D ultrasound, allows for a whole assessment of relevant vessels and quantitative assessment of vessel density and perfusion within a specified area.  Faridpur Med. Coll. J. Jul 2018;13(2): 97-100